Uma análise histórica e econométrica dos fatores associados ao cultivo de coca na Colômbia - Santos, Cézar Augusto Pereira dos (2021)
Together, Colombia, Peru and Bolivia account for more than 98% of the global area of coca crops, the main input for the manufacture of cocaine. Colombia is responsible for approximately 70% of the total cultivated. The choice of this theme as object of analysis is due to the country's importance in the world cocaine market and its geographical proximity to Brazil - the world's second largest consumer of cocaine. This research carried out a spatial analysis of crops in Colombian municipalities between 2001 and 2009 from a set of economic variables / social, environmental, violence and political strategies adopted from Plan Colombia to face the supply of cocaine. Thus, it was held, at first, one Exploratory Spatial Data Analysis (ESDA), and, subsequently, an econometric model of spatial cross-section for the year 2009 and a data model in spatial panel for the period between 2001 and 2009 were estimated. Among the results, it was found that the main strategy adopted under the Plan was the forced eradication of crops, with emphasis on aerial eradication with the use of glyphosate. In the period under analysis, approximately one million hectares of coca were fumigated and about three hundred and twenty thousand were eradicated manually. In both 2001 and 2009, there was a spatial dependence between crops in Colombian municipalities, with a tendency to concentration. In 2001, the main regional cluster was located in the southeastern part of the country, mainly in the department of Putumayo, in the Amazon region. In 2009, it was located in the southwestern part, in the department of Nariño, in the Pacific region, showing that the crops migrated in response to the eradication strategies adopted by the government. In estimating the cross-section spatial econometric model, a SAC model was chosen. In the case of the spatial panel data model, the choice fell on the SAR model. The crops had a direct relationship with the eradicated hectares and with the presence of illegal armed groups. The relationship proved to be inverse with the IDM and government investments in the municipalities, which in turn had little impact on the reduction of crops. This reflects the choice of Governments, which under Plan Colombia contributed most of the financial resources (82%) to the military component of the Plan - and, also due to the fact that during the period under analysis, it adopted as a state policy the prohibition of implementing Alternative Development (AD) projects in municipalities where the presence of coca crops was identified.